Public Awareness to Good Governance Management of Paikhaew Sub-district Administration Organization in Sawangarom District, Uthaithani Province - Kesthong, Thanee; Metheevarachatra, Anond; Thuenchang, Worrakrit; Tongmun, Winai; Thosakri, Thanong (Journal of Thammawat, 2024)
The objectives of this research were: 1. Study about the administration level as the good governance principle of Paikhaew Subdistrict Administration Organization Office, Sawangarom district, Uthaithani province as the citizen’s aesthesia, and 2. Compare about the management level as the good governance principle of Paikhaew Subdistrict Administration Organization Office, Sawangarom district, Uthaithani province as the citizen’s aesthesia which categorizing by the citizen’s characteristic. The sampling group of this research is the citizen of Paikhaew subdistrict, Sawangarom district, Uthaithani province for 353 people. The data collection instrument is the questionnaire which evaluates by rating scale (5 levels). The reliability value is 0.97. The statistics which use to analyze are frequency, percentage, mean, standard deviation (SD), t-test independent, and One Way ANOVA. The research result presented that: The overall administration of good governance principle of Paikhaew Subdistrict Administration Organization Office, Sawangarom district, Uthaithani province as the citizen’s aesthesia is on the high level in every field (= 4.37). Management is at a high level. The first priority is the responsibility (= 4.50), followed by the rule of law (= 4.46), the principle of value (= 4.43), the risk principle (= 4.42), the major aspects (= 4.28), which are managed sequentially. The last is the principle of participation. (= 4.23). The comparison administration result of good governance principle of Paikhaew Subdistrict Administration Organization Office, Sawangarom district, Uthaithani province as the citizen’s aesthesia are similar which categorizing by the citizen’s characteristic which consists of the gender